1988
DOI: 10.1136/ard.47.5.414
|View full text |Cite
|
Sign up to set email alerts
|

Differential response to compressive loads of zones of canine hyaline articular cartilage: micromechanical, light and electron microscopic studies.

Abstract: SUMMARY Thin (100 urm) perpendicular slices of canine femoral condylar cartilage were placed horizontally on the stage of a Nachet microscope and viewed by transmitted light in the differential interference contrast mode. Each slice was held on the microscope stage by a loading rig and tested mechanically in compression. Measured loads to a maximum of -2-3 MN/M2 were applied to the end of the slice corresponding to the articular surface. Photographs were taken of the cartilage before and during loading, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
0
3

Year Published

1990
1990
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(29 citation statements)
references
References 8 publications
4
22
0
3
Order By: Relevance
“…Other studies of tissueengineered cartilage have also observed that increased relative proteoglycan content of the tissue correlated with improved compressive mechanical properties [ 12, 331. This trend is similar to that observed in native articular cartilage [31] as both the relative proteoglycan content of the tissue [3,14,22,2.5,32,3.5,39] and its compressive stiffness [38,44,4.5] increase with increasing depth from the articular surface. However, there is some debate as to whether the intermediate-zone [38] or DEEP [44,4.5] has the highest compressive stiffness of the native tissue.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Other studies of tissueengineered cartilage have also observed that increased relative proteoglycan content of the tissue correlated with improved compressive mechanical properties [ 12, 331. This trend is similar to that observed in native articular cartilage [31] as both the relative proteoglycan content of the tissue [3,14,22,2.5,32,3.5,39] and its compressive stiffness [38,44,4.5] increase with increasing depth from the articular surface. However, there is some debate as to whether the intermediate-zone [38] or DEEP [44,4.5] has the highest compressive stiffness of the native tissue.…”
Section: Discussionsupporting
confidence: 82%
“…This trend is similar to that observed in native articular cartilage [31] as both the relative proteoglycan content of the tissue [3,14,22,2.5,32,3.5,39] and its compressive stiffness [38,44,4.5] increase with increasing depth from the articular surface. However, there is some debate as to whether the intermediate-zone [38] or DEEP [44,4.5] has the highest compressive stiffness of the native tissue. It was for this reason that a combined population of intermediate and DEEP chondrocytes was included in this study.…”
Section: Discussionsupporting
confidence: 82%
“…In contrast, strenuous exercise (20 km/d) decreases the GAG concentration within the extracellular matrix and does not increase the stiffness of articular cartilage (Jurvelin et al, 1986;O'Connor et al, 1988;Kiviranta et al, 1988). Similar to canines, in horses it has been hypothesized that regular joint loading during youth is important for the development of a well organized and strong articular cartilage collagen network (Brama et al, 2000 andHelminen et al, 2000).…”
Section: Articular Cartilagementioning
confidence: 99%
“…Estas macromoléculas são importantes na hidratação da matriz, estabilização da rede colágena, que por sua vez influenciam na resistência a forças compressivas e atuam como filtro regulando a passagem de moléculas através do meio extracelular (ALBERTS et al, 1999;CULAV et al, 1999;HARDINGHAM et al, 1992;HUBER et al, 2000;MAROUDAS 1976;O'CONNOR, 1988;BRANDT 1981;MUIR 1983;SÄÄMÄMEN et al, 1994;WIGHT et al, 1991).…”
Section: )unclassified